Variation in Selenium Tolerance, Accumulation, and Growth Parameters of Different Wheat Cultivars. Issue 2 (19th January 2016) - Sharma, Sucheta; Gupta, Rahul; Singh, D.
ABSTRACT: In a greenhouse experiment, wheat cultivars PDW 291, PBW 550, and TL 2908 were grown in alkaline sandy-loam soil treated with sodium selenate at 0, 2, and 4 mg selenium (Se) kg −1 soil. Selenate-treated wheat plants accumulated greater Se in roots, stems, leaves, and grains and showed growth retardation, snow-white chlorosis, decreased shoot length and chlorophyll, and reduced leaf area and produced less number of grains as compared to control plants. Maximum reduction in these parameters was observed in selenate-treated TL 2908 plants and most of the plants died before maturity with almost no grain formation with 4 mg Se kg −1 soil. Selenium accumulation resulted in decreased reducing sugar, starch, and protein contents in grains whereas total free amino acids increased significantly in all the three cultivars. Selenium accumulation in wheat showed metabolic disturbances and its accumulation in grains was beyond toxic levels, thus making it unfit for consumption.